The pursuit of possibility : redesigning research universities - Thrift, Nigel (Policy Press, 2022)
Nigel Thrift explores recent changes in the British research university that threaten to erode the quality of these higher education institutions. He considers what a research university has now become by examining the quandaries that have arisen from a succession of misplaced strategies and false expectations.